THE ISSUES OF FUNDING OF POLITICAL PARTIES IN LITHUANIA FROM THE PERSPECTIVE OF PRIVATE LAW - Jurkevicius, Vaidas; Tamosiuniene, Egidija (European Scientific Journal, ESJ, 2013)
The funding of political parties is usually understood exclusively as an institution of public law. This research reveals that the relations of property acquisition by political parties gratuitously (funding) may also be attributed to the object of regulation of private law. When the funding of political parties considered not only from the perspective of public law but also from the point of view of private law, it becomes possible to apply other regulation principles than it is usual to these relations. Such principles underpin the analysis of specific practical issues related to the funding of political parties, including also the amendments to the Law on Funding of, and Control Over Funding of, Political Parties and Political Campaigns, which came into force as of 1 January 2012 and which imposed a ban on legal entities and a restriction on individuals to make donations to political parties.